Acceptance of massive open online course as a supplementary learning tool in higher education - R.Azami, Husna Hafiza (2020)
Massive Open Online Course (MOOC) is an innovative and viable alternative to complement the conventional classroom education. Since the development of this technology may entail huge investment and arduous effort, it is crucial to understand the factors that influence this technology acceptance before it is developed. Even though there have been existing research that studied the acceptance of MOOC, there are very limited literatures that discuss it in the context of Malaysia and the use of it as a supplementary learning tool. Therefore, the objective of this research is to identify, propose and evaluate a model for measuring the acceptance of this technology as a supplementary learning tool among undergraduate students in a university in Malaysia. A systematic literature review was done to identify and propose a MOOC acceptance model. A prototype was then developed based on Chemical Equilibrium chapter in Chemistry subject to satisfy target users’ needs. The prototype was assessed through usability evaluation and the acceptance model which was based on Technology Acceptance Model (TAM) was evaluated among students who undertake Chemistry course in the same university. The quantitative data obtained from 111 students through a questionnaire (eight constructs and 39 items) was analysed using SPSS and SmartPLS 3.0. Findings showed positive perception of students towards the use of MOOC. Partial least squares structural equation modelling (PLS-SEM) analysis showcased nine out of ten relationships were found to be significant. To gain better understanding of these statistical results, qualitative data was then collected via semi-structured group interview with five survey respondents. The data was analysed using deductive content analysis and the findings managed to confirm and expand the empirical study. The model proposed in this research as well as the MOOC acceptance findings provide relevant theoretical contribution to be further validated and explored by future researchers. On the other hand, the development process and the developed prototype incorporating the design criteria suggested by scholars offer practical contribution which can help developers in designing a MOOC that can be accepted by students.